TINJAUAN KRIMINOLOGIS TENTANG ABORSI YANG DILAKUKAN OLEH DUKUN BERANAK DI KOTA KUPANG (Studi Kasus di Kelurahan Kuanino Kecamatan Kota Raja Kota Kupang) - Hamma, Grace Ivolia Putri; Manuain, Orpa Ganefo; Sonbait, Sigit Prabowo (Petitum Law Journal, 2025)
Lack of awareness of the risks of casual sex leads to unwanted pregnancies. Issue of abortion has taken center stage in global politics and is no longer taboo. In Indonesia, abortion is illegal except in medical cases or rape as per the 2009 Health Law. The Criminal Code protects the fetus and understanding the motives for abortion is important in law. Illegal abortion practices are common, including in Kuanino Village, where abortion recidivists continue to perform abortions. The motives of the perpetrators in performing abortions in Kuanino Village are economic and experience in performing abortions. Abortions performed by village traditional healers are motivated by their expertise. The act of abortion that occurred in Kupang City is by sequencing. The modus operandi of the abortion crime is that the abortionist is given traditional medicine periodically according to the time determined by the traditional birth attendant. The second way is that the abortionist's genitals are inserted with roots and wood that function to accelerate the process of abortion. Obstacles in overcoming abortion cases in Kupang City are lack of legal awareness, lack of law enforcement efforts, and covert abortion practices. Suggestions include education, access to health services, and stricter law enforcement.